Diseño de una propuesta técnica de un bar restaurante - Samaniego Gancino, Rodrigo Francisco (2020)
The technical proposal presented below is for the development of a bar restaurant to be located in Quito. The proposal is based on concepts and definitions of various aspects which are essential and provide a theoretical basis for the creation and design of the proposal in order to be clear about what is necessary for the approach, specially to conceptualize consumption trends and food and beverage establishment management. Immediately a diagnosis will be made by which the behavior of the market, the way of consumption of a previously raised target audience, their preferences, tastes and electives will be determined to expose how this proposal can be raised and what guidelines must be taken to make it viable. Subsequently, with the theoretical and research information, the proposal is generated as such with each and every of the components such as the brand, the product proposal with the respective cost and finally the financial component with the investment plan and the projections. All this with the aim of proposing a well-founded technical proposal to have a profitable food and beverage business model suitable for the proposed target audience.